Pembelajaran Discovery Learning Dan Berpikir Kritis Pada Mata Pelajaran IPS Peserta Didik Sekolah Dasar - Sulvahrul Amin; Jamaluddin Arifin; Nadia Aghni Izzani Anisyar (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The aim of this study was to investigate the implementation of Discovery Learning in fostering critical thinking skills among fifth-grade students in Social Studies at SD Inpres Pangkabinanga, Pallangga District, Gowa Regency. Additionally, it sought to determine the forms of development of critical thinking skills among these students. The research employed a qualitative descriptive method, utilizing data collection techniques such as interviews, observations, and documentation. Data analysis involved data reduction, data presentation, and drawing conclusions. The findings revealed that the implementation of Discovery Learning in fostering critical thinking skills among fifth-grade students at SD Inpres Pangkabinanga was generally effective, though there were shortcomings in the reflection stage. The development of critical thinking skills among these students was gradually progressing and well-realized during the stages of Discovery Learning, with indicators including communication, creativity, problem-solving, openness, argumentation, confidence, analytical thinking, and rational and logical thinking. However, some indicators of skill development were not optimal due to factors such as shyness, lack of interest, or excessive joking among some students. Nevertheless, these issues could be addressed by teachers through motivating and maintaining classroom focus during the learning process. Notably, students demonstrated good proficiency in argumentation, problem-solving, analytical thinking, and rational and logical thinking, while areas needing improvement included communication, openness, creativity, and confidence.